Antenatal care coverage in a low-resource setting: Estimations from the Birhan Cohort. - Clara Pons-Duran; Delayehu Bekele; Sebastien Haneuse; Bezawit Mesfin Hunegnaw; Kassahun Alemu; Munir Kassa; Yifru Berhan; Frederick G B Goddard; Lisanu Taddesse; Grace J Chan (Public Library of Science (PLoS), 2023)
Antenatal care (ANC) coverage estimates commonly rely on self-reported data, which may carry biases. Leveraging prospectively collected longitudinal data from the Birhan field site and its pregnancy and birth cohort, the Birhan Cohort, this study aimed to estimate the coverage of ANC, minimizing assumptions and biases due to self-reported information and describing retention patterns in ANC in rural Amhara, Ethiopia. The study population were women enrolled and followed during pregnancy between December 2018 and April 2020. ANC visits were measured by prospective facility chart abstraction and self-report at enrollment. The primary study outcomes were the total number of ANC visits attended during pregnancy and the coverage of at least one, four, or eight ANC visits. Additionally, we estimated ANC retention patterns. We included 2069 women, of which 150 (7.2%) women enrolled <13 weeks of gestation with complete prospective facility reporting. Among these 150 women, ANC coverage of at least one visit was 97.3%, whereas coverage of four visits or more was 34.0%. Among all women, coverage of one ANC visit was 92.3%, while coverage of four or more visits was 28.8%. No women were found to have attended eight or more ANC visits. On retention in care, 70.3% of participants who had an ANC visit between weeks 28 and <36 of gestation did not return for a subsequent visit. Despite the high proportion of pregnant women who accessed ANC at least once in our study area, the coverage of four visits remains low. Further efforts are needed to enhance access to more ANC visits, retain women in care, and adhere to the most recent Ethiopian National ANC guideline of at least eight ANC visits. It is essential to identify the factors that lead a large proportion of women to discontinue ANC follow-up.